A miRNA-145/TGF-β1 negative feedback loop regulates the cancer-associated fibroblast phenotype. (28th February 2018) - Melling, Genevieve E; Flannery, Sarah E; Abidin, Siti A; Clemmens, Hannah; Prajapati, Priyanka; Hinsley, Emma E; Hunt, Stuart; Catto, James W F; Coletta, Ricardo Della; Mellone, Massimiliano; Thomas, Gareth J; Parkinson, E Ken; et al.
Abstract : CAF contribute to immune evasion, therapy resistance and metastasis of tumours. The presence of myofibroblastic CAF correlates with poor survival, but the mechanisms by which they are generated are poorly understood. Here, we identify a microRNA, miR-145, which inhibits and reverses myofibroblast differentiation by acting in a negative feedback loop with transforming growth factor β1. This reveals a novel mechanism underlying myofibroblast and CAF development that may offer therapeutic opportunities. Abstract: The dissemination of cancer cells to local and distant sites depends on a complex and poorly understood interplay between malignant cells and the cellular and non-cellular components surrounding them, collectively termed the tumour microenvironment. One of the most abundant cell types of the tumour microenvironment is the fibroblast, which becomes corrupted by locally derived cues such as TGF-β1 and acquires an altered, heterogeneous phenotype (cancer-associated fibroblasts, CAF) supportive of tumour cell invasion and metastasis. Efforts to develop new treatments targeting the tumour mesenchyme are hampered by a poor understanding of the mechanisms underlying the development of CAF. Here, we examine the contribution of microRNA to the development of experimentally-derived CAF and correlate this with changes observed in CAF derived from tumours. Exposure of primary normal human fibroblasts to TGF-β1 resulted in the acquisition of a myofibroblastic CAF-like phenotype. This was associated with increased expression of miR-145, a miRNA predicted in silico to target multiple components of the TGF-β signalling pathway. miR-145 was also overexpressed in CAF derived from oral cancers. Overexpression of miR-145 blocked TGF-β1-induced myofibroblastic differentiation and reverted CAF towards a normal fibroblast phenotype. We conclude that miR-145 is a key regulator of the CAF phenotype, acting in a negative feedback loop to dampen acquisition of myofibroblastic traits, a key feature of CAF associated with poor disease outcome.